Drivers affecting the adoption and effectiveness of social media investments: The Italian wine industry case. Issue 2 (7th June 2019) - Galati, Antonino; Tinervia, Salvatore; Tulone, Antonio; Crescimanno, Maria
Abstract : Purpose: The purpose of this paper is twofold: first, to identify distinct organisational models in a sample of firms operating in the wine industry; and second, to identify the main internal resources that characterise those firms most motivated towards the adoption of social media (SM) tools and those that perceive SM investment as more effective. Design/methodology/approach: The empirical investigation was carried out by administering an online questionnaire to a sample of 82 Sicilian wineries. The principal component analysis was used to identify latent factors that drive managers to invest in SM technologies and to measure the impact perceived by managers. Subsequently, a cluster analysis was performed to identify similar organisational models. Findings: The findings show that large wineries with a high number of employees possessing knowledge and skills in regard to SM tools and social network (SN) management are highly motivated towards the adoption of SM and perceive their SM investment as more effective. Research limitations/implications: The main limitation of the paper lies in the limited sample size, which does not allow the results to be generalised. Practical implications: The findings provide support for managers, who could use these results to better focus their investment on infrastructure that facilitates the development of specific skills needed to manage SM tools and SNs, as well as customer relations. Originality/value: To date, very few empirical studies have focussed on providing evidence on the role and impact of SM integration into the marketing communication plan of a strategic industry, such as the wine industry.